KETERAMPILAN MENYIMAK DONGENG SISWA KELAS VII SMPN 2 BUKIT SUNDI KABUPATEN SOLOK DENGAN MENGGUNAKAN MEDIA AUDIO TAHUN PELAJARAN 2013/2014 - Nela, Riska Ilfia; Mana, Lira Hayu Afdetis; Andeska, Harry (Pendidikan Bahasa Indonesia, 2014)
Based on the background of this study as follows . First , the low skills of the students in understanding the oral discourse . Second , the lack of students in listening comprehension . Third , the lack of media or facilities to support learning to listen , including listening to fairytales .Based on the results of research on listening skills class VII SMP fable 2 Solok Bukit Sundi use of audio media , it can be concluded that fairy tales listening skills are at the level of qualification well with the average value in the range of 86-95 % 89.81berada . From the results obtained by the indicator , it can be concluded the average value of the indicator 1 students write the contents of a fairy tale the mean ( M ) 85.52 % are in the range of 76-85 % on qualifying Being Good ( Good ) . In the second indicator in the message write obtaining the mean ( M ) of 84.65 % in the range of 76-85 % . Being good in qualifying . At 3 in the write indicator figures derive the mean ( M ) of 100 % at the range of 96-100 % . Perfectly located on qualifications . At 4 in the write indicator obtaining background mean ( M ) of 80.70 was in the range of 96-100 % . Both are on the qualifications ( Good )